The Analysis Of Code Mixing In Maudy Ayundaâ€™s Vlog â€œStress Managementâ€ - Nita Dianah; Hanif Nurcholish Adiantika; Susilawati Susilawati (Universitas Subang, 2025)
Nowadays, many people use code-mixing in their daily lives. Therefore, content creators use it as a tool to introduce culture and provide information to audiences who may not be familiar with the language. This research decided to find the types of code-mixing in Maudy Ayunda's